2020
DOI: 10.1111/sms.13780
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding high‐risk rotator cuff loading: Muscle force during three pull‐up techniques

Abstract: Heavily loaded overhead training tasks, such as pull-ups are an effective strength training and rehabilitation exercise requiring high muscle forces maintained over a large range of motion. This study used experiments and computational modeling to examine loading patterns during three different pull-up variants and highlighted risks to vulnerable musculoskeletal structures. Optical motion tracking and a force platform captured kinematics and kinetics of 11 male subjects with no history of shoulder pathology, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The susceptibility of the shoulder complex to RT-related injuries is due in part to the stress placed on a joint that is anatomically non-load-bearing but assumes the role of an active joint with high-load repetitive lifting [42]. For example, impingement injuries are possible when the subacromial space is at its smallest, at 120 • humeral elevation, 90 • abduction, and 45 • external rotation [65]. This position is reached during the pull-up motion (when supraspinatus is most active), especially with a narrow grip such as during front and reverse pull-ups (since it increases the required abduction moment).…”
Section: Case Study/ Quantitative Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The susceptibility of the shoulder complex to RT-related injuries is due in part to the stress placed on a joint that is anatomically non-load-bearing but assumes the role of an active joint with high-load repetitive lifting [42]. For example, impingement injuries are possible when the subacromial space is at its smallest, at 120 • humeral elevation, 90 • abduction, and 45 • external rotation [65]. This position is reached during the pull-up motion (when supraspinatus is most active), especially with a narrow grip such as during front and reverse pull-ups (since it increases the required abduction moment).…”
Section: Case Study/ Quantitative Analysismentioning
confidence: 99%
“…This position is reached during the pull-up motion (when supraspinatus is most active), especially with a narrow grip such as during front and reverse pull-ups (since it increases the required abduction moment). Nevertheless, wide pull-ups reduce the high stresses in both the deltoid and supraspinatus by emphasizing the back muscles (i.e., latissimus dorsi, trapezius, and rhomboid major) [65]. It is noteworthy that the injury risk might be higher when the fatigue level rises due to the increased eccentric loading on the supraspinatus.…”
Section: Case Study/ Quantitative Analysismentioning
confidence: 99%
“…During the pull-up exercise, there are substantial differences in muscle activation when the width between hands or the forearm orientation (intended according to supinated or pronated pull-ups) changes. In fact, differences are present both for a smaller bending of the elbow and for the different working planes of the humerus [1,11,22]. Urbanczyk et al [22] reported that during wide pull-ups the latissimus dorsi was more active than in pronated shoulder width pull-ups (in which biceps brachii and brachialis activation was prevalent) and supinated pull-ups (in which rotator cuff activation was prevalent).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, differences are present both for a smaller bending of the elbow and for the different working planes of the humerus [1,11,22]. Urbanczyk et al [22] reported that during wide pull-ups the latissimus dorsi was more active than in pronated shoulder width pull-ups (in which biceps brachii and brachialis activation was prevalent) and supinated pull-ups (in which rotator cuff activation was prevalent). Lusk et al [11] found that wide-width lat pull-down did not significantly influence the latissimus dorsi activation, which seems to be more active with a pronated than a supinated grip, although analysed during lat pull-down exercise (performed using a lat machine).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation